2020
DOI: 10.5391/ijfis.2020.20.4.358
|View full text |Cite
|
Sign up to set email alerts
|

A Fuzzy Decision Support System for Diagnosis of Some Liver Diseases in Educational Medical Institutions

Abstract: Decision support systems improve medical diagnosis and minimize diagnostic errors. Existing diagnostic systems are often complex and exhibit limited performance on liver diseases, particularly the liver cancer. This paper presents a fuzzy decision support system for helping students diagnose some human liver diseases in educational medical institutions. The proposed system aims to improve real medical diagnosis processes. The approach has three basic steps: 1) symptoms-based diagnosis, 2) liver function-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The fuzzy expert system (FES) algorithm is simple and involves only IF-THEN rules. Previous studies have reported the FES in detail [24][25][26][27][28][29][30][31][32][33] and is modeled to determine fault locations [34]. The FES was provided for location determination by considering the impedance values as inputs [35].…”
Section: Introductionmentioning
confidence: 99%
“…The fuzzy expert system (FES) algorithm is simple and involves only IF-THEN rules. Previous studies have reported the FES in detail [24][25][26][27][28][29][30][31][32][33] and is modeled to determine fault locations [34]. The FES was provided for location determination by considering the impedance values as inputs [35].…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of this study is how to see the success of the application of the Sugeno fuzzy inference system in determining the level of risk of obesity in children, as for reasons uses the Fuzzy Sugeno inference system because the technique can approach reasoning, especially in systems that deal with problems that are difficult to define using mathematical models. Fuzzy Sugeno has also been shown to provide excellent results when applied in various cases, for example a study conducted by [14] in evaluating kidney function, then a study conducted by [15] on diagnosing liver disorders, then [16] conducted a study on the diagnosis of hepatitis B. The fuzzy inference system has also been used by [17], [18] in his research to detect diabetes mellitus and diagnose colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%